Intermediate‐term outcome of single kidney grafts from pediatric donors weighing 10–14 kg in adult recipients. (26th March 2013) - Gröschl, Isabel; Wolff, Thomas; Gürke, Lorenz; Eugster, Thomas; Hopfer, Helmut; Steiger, Jürg; Schaub, Stefan; Burkhalter, Felix
Abstract Background Kidneys from pediatric donors weighing <10 kg are preferably transplanted en bloc, while kidneys from donors weighing >15 kg can be safely transplanted as single kidneys. However, single kidney transplantation from donors weighing 10–14 kg is controversial and has not been well investigated. Methods We analyzed the outcome of 15 recipients of single kidneys from donors weighing 10–14 kg (study group) with 40 recipients receiving an allograft from ideal deceased donors (control group). Results After a follow‐up of three yr, death‐censored graft survival was 100% in both groups. The calculated creatinine clearance was lower in the study group at six months (53 vs. 71 mL/min; p = 0.01) and similar at 12 months (68 vs. 68 mL/min; p = 0.48), 24 months (81 vs. 70 mL/min; p = 0.58), and 36 months (74 vs. 69 mL/min; p = 0.59). Urinary albumin/creatinine ratios were comparable between the two groups up to two yr. At three yr, urinary albumin/creatinine ratios were higher in the study group than the control group (10.5 vs. 0.9 mg/mmol; p = 0.007). Surveillance biopsies at three and six months post‐transplant revealed no evidence for focal segmental glomerulosclerosis in the study group. Conclusions Transplantation of single pediatric kidneys from donors weighing 10–14 kg into adult recipients provides excellent intermediate‐term outcomes. Low‐grade albuminuria, three yr post‐transplant, might indicate late‐onset hyperfiltration injury.